2007
DOI: 10.1021/ic061765w
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal Growth and Characterization of Disilver(I) Monofluorophosphate(V), Ag2PO3F:  Crystal Structure, Thermal Behavior, Vibrational Spectroscopy, and Solid-State19F,31P, and109Ag MAS NMR Spectroscopy

Abstract: Single crystals of disilver(I) monofluorophosphate(V), Ag2PO3F (1), were obtained by slow evaporation of a diluted aqueous Ag2PO3F solution. Compound 1 adopts a new structure type and crystallizes in the monoclinic space group C2/c with eight formula units and lattice parameters of a = 9.2456(8) A, b = 5.5854(5) A, c = 14.7840(13) A, and beta = 90.178(2) degrees. The crystal structure of 1 [R(F2 > 2sigma(F2) = 0.0268, wR(F2 all) = 0.0665] is composed of three crystallographically independent Ag+ cations and PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
(36 reference statements)
5
15
0
Order By: Relevance
“…As has been shown for the thermal behavior of the hydrous species Ca(PO 3 F)(H 2 O) 2 , [37,38] Sr(PO 3 F)(H 2 O), [20,37] and Mg(NH 4 ) 2 ((PO 3 F)) 2 [39] or the anhydrous species Ag 2 (PO 3 F) [8] and Hg 2 (PO 3 F), [10] multi-stage decomposition mechanisms including elimination of POF 3 (for all species), H 2 O and HF (for hydrous species) were proposed for the decompositions, as substantiated by simultaneous mass spectrometric analyses of the gaseous decomposition products.…”
Section: Thermal Behaviormentioning
confidence: 56%
See 1 more Smart Citation
“…As has been shown for the thermal behavior of the hydrous species Ca(PO 3 F)(H 2 O) 2 , [37,38] Sr(PO 3 F)(H 2 O), [20,37] and Mg(NH 4 ) 2 ((PO 3 F)) 2 [39] or the anhydrous species Ag 2 (PO 3 F) [8] and Hg 2 (PO 3 F), [10] multi-stage decomposition mechanisms including elimination of POF 3 (for all species), H 2 O and HF (for hydrous species) were proposed for the decompositions, as substantiated by simultaneous mass spectrometric analyses of the gaseous decomposition products.…”
Section: Thermal Behaviormentioning
confidence: 56%
“…In previous studies on monofluorophosphates we reported syntheses, structure determinations, and properties of some of these compounds. In particular, we have investigated the structural effects that are caused by incorporation of the (PO 3 F) 2-anion in combination with counter cations that have closed electron shells (Sr, [6] Ba, [7] Ag, [8,9] Hg [10] ) In continuation of these studies we became interested in divalent first-row transition metal monofluorophosphates. So far, structural studies of this family of compounds had been restricted to a few members, comprising the three hydrous phases Zn(PO 3 F)(H 2 O) 2.5 , [13] Cu(PO 3 F)(H 2 O) 2 , [14] and Co(PO 3 F)(H 2 O) 3 [15] [It should be noted that compounds with composition M 2 (PO 4 )F (M = Mn, Cu, Cd) [11] or www.zaac.wiley-vch.de…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Although the synthesis of Ag 2 PO 3 F has been already described, [2] its crystal structure was unknown until very recently. [3] During the experiments performed to grow Ag 2 PO 3 F single crystals from aqueous AgNO 3 and (NH 4 ) 2 PO 3 F solutions, the generation of another, unknown, phase was established. Crystals of the new compound, finally identified as NH 4 Ag 3 (PO 3 F) 2 , could be obtained and its structure was eventually determined by single-crystal x-ray diffractometry after adjusting the experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization from the remaining ®ltrate then leads to single-phase products. Although the preparation of Ag 2 PO 3 F was described a long time ago (Lange, 1929), its crystal structure was unknown until very recently (Weil et al, 2007). During single-crystal growth experiments aimed at Ag 2 PO 3 F from aqueous AgNO 3 and (NH 4 ) 2 PO 3 F solutions, crystals of NH 4 Ag 3 (PO 3 F) 2 were obtained serendipitously, and the crystal structure of this new compound is reported here.…”
Section: Commentmentioning
confidence: 87%